Individual and combined effect of salinity and nitrite on freshwater Anammox bacteria (FAB). (1st February 2020) - Lin, Limin; Pratt, Steven; Rattier, Maxime; Ye, Liu
Abstract: Anaerobic ammonium oxidation (Anammox) based technology has potential for nitrogen removal from wastewater with high salinity, but both salt and nitrite (a substrate for Anammox) have negative effect on microbial activity. In order to achieve Anammox in saline wastewater treatment, it is essential to understand the combined effect of these two components. In this study, the individual and combined effect of salinity and nitrite on fixed film freshwater Anammox bacteria (FAB, mainly belonging to the Ca. Brocadia genus), enriched on carriers from a 1500 L pilot scale one-stage (PN/Anammox) moving bed bioreactor (MBBR), were systematically investigated by 57 pre-designed batch tests. The combined inhibition of nitrite and salinity was determined by comparing with additive and independent inhibition models. With salinity only, the specific Anammox activity (SAA) decreased with increasing salinity: 14.6 mS/cm (about 9.1 g NaCl/L) of salinity caused 50% inhibition (IC50 ). With nitrite only, SAA started to decrease when nitrite concentration was above 450 mg N/L (threshold) and decreased with increased nitrite (IC50  = 666 mg N/L) thereafter. Significantly, when both salinity and nitrite were elevated, both the threshold and IC50 of nitrite were reduced, with inhibition enhanced. Analysis showed that at high salinity (>14.6 mS/cm) and nitrite concentration (>666 mg N/L), inhibition was close to that predicted by simulation of additive and independent inhibition models. Within a salinity range of 4–14.6 mS/cm and nitrite concentration range of 50–666 mg N/L, the combined inhibition was more severe than prediction (p < 0.05) based on the additive and independent inhibition models and therefore it was determined to be synergistic inhibition. Graphical abstract: Image 1 Highlights: The individual and combined effect of salinity and nitrite on FAB was systematically studied. Anammox activity decreased with increased salinity, with the IC50 observed at 14.6 mS/cm. Anammox activity was unaffected by nitrite concentration up to 450 mg N/L; IC50 was 666 mg N/L. Combined inhibitory effect was synergistic at low salt and nitrite concentration. Nitrite accumulation under elevated salinity will likely result in synergistic inhibition.